Specific Surface Area Enhancement of Waste Tire-Based Activated Carbon by Demineralization Technique and Adsorption of Methylene Blue - Estifanos Kassahun; Sintayehu Mekuria; Surafel Mustefa Beyan (International Journal of Chemical Engineering)
This study was focused on the synthesis of activated carbon from a waste tire and the enhancement of its specific area by a demineralization technique that can be used for the removal of methylene blue dye (MB). Maximum MB removal (89.41%) was attained at an impregnation ratio value of 0. A maximum yield (42.65%) was found at 48 h. Waste tire-based activated carbon (WTAC)'s ability to remove MB was increased by large values up to an impregnation time of 24 h. WTAC has a maximum MB removal of 90.13% at 4 M of KOH. The sample had a surface area of 53 m2/g. This sample was demineralized by using NaOH and H2SO4 in a 1 : 1 ratio, and the surface area was enhanced to 257 m2/g. In the demineralization process, a massive decrement of metals from the waste was seen; for each metal, namely, Zn2+, Al3+, Ca2+, and Mg2+, 43.79%, 32.45%, 27.95%, and 6.843% reductions were achieved, respectively. After this process, the maximum removal of MB was found at 1.2 g adsorbent dosage, 120 min, pH 8, the temperature of 20°C, and an initial dye concentration of 10 mg/L. The adsorption mechanism revealed that the process of adsorption happens at a specific site of homogeneous adsorption on the surface of the adsorbent. The kinetics study showed that the adsorption process of the dye is mainly affected by the chemical reaction.